CONQUERING THE PUBLISHING SILENCES OF BLACK ACADEMIC WOMEN - Rhoda, Anthea; Maurtin-Cairncross, Anita; Phillips, Julie; Witbooi, Sarah (Journal of Community and Health Sciences, 2020)
Introduction: Although women fulfil and play meaningful roles in the academic life of universities, their contributions have seldom been acknowledged. The voices of women outside of the dominant western context of knowledge production, such as women in South African historically black universities (HBUs), remain largely marginalized. Women at these HBUs have indicated a need for mentoring and support to assist with their scholarly endeavours. Objectives: The objective of the present study was to determine the participants' views on the ways in which the mentoring process was used to overcome the challenges of publishing their academic work. Methods: Using a qualitative method and a focus group discussion to collect data. Participants: Lecturers who attended an academic writing skills development program. Setting: University of the Western Cape. Intervention: Academic writing skills development program. Results: The findings of this study indicates that dedicated time, learning to write, a supportive network and a culture of publishing in the institution was needed to assist black academic women conquer their publishing silences. Conclusion: A mentoring process can facilitate academic publication output.